2010
DOI: 10.1002/lary.20961
|View full text |Cite
|
Sign up to set email alerts
|

Demographic disparities among children with frequent ear infections in the United States

Abstract: Despite increasing awareness, there are still notable racial/ethnic and socioeconomic disparities among children with FEI. Further efforts to eliminate these disparities and improve the care of children with FEI are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 18 publications
1
53
0
Order By: Relevance
“…A National Health Insurance Survey (NHIS) by Vakharia et al of more than 7 million American children demonstrated a higher prevalence of frequent ear infections (greater than 3 acute otitis media episodes over the course of 1 year) in white children when compared with Black/ African American and Hispanic/Latino children. 1 An older NHIS study by Lanphear et al also demonstrated similar results with respect to race/ethnicity, as well as poverty status, in terms of its association with less frequent recurrent acute otitis media. 19 Auinger et al showed a higher prevalence of otitis media in Caucasian children based on the Third Nutritional Health and Nutrition Examination Survey.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A National Health Insurance Survey (NHIS) by Vakharia et al of more than 7 million American children demonstrated a higher prevalence of frequent ear infections (greater than 3 acute otitis media episodes over the course of 1 year) in white children when compared with Black/ African American and Hispanic/Latino children. 1 An older NHIS study by Lanphear et al also demonstrated similar results with respect to race/ethnicity, as well as poverty status, in terms of its association with less frequent recurrent acute otitis media. 19 Auinger et al showed a higher prevalence of otitis media in Caucasian children based on the Third Nutritional Health and Nutrition Examination Survey.…”
Section: Discussionmentioning
confidence: 68%
“…2 In the United States, the annual cost of treatment for otitis media to include medical and surgical intervention is estimated between $3 billion and $5 billion. 1,2 Previously reported intrinsic otitis media risk factors include low birth weight, male gender, and age younger than 7 years old. Extrinsic risks have included day care attendance, presence of siblings in the household, smokers in the household, and lack of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated similar rates of RAOM and OME between black and white children, while others found higher rates of OME among black children and in children who are publicly insured 37,38 . Regarding RAOM, higher rates of frequent OM (defined as 3 or more episodes of OM in the past 12 months) have been found among white children and among children living below poverty, whereas other studies have found a higher prevalence of frequent OM in more affluent children 40,41 .…”
Section: 4 Discussionmentioning
confidence: 91%
“…The National Health Interview Survey (NHIS), conducted by the National Center for Healthcare Statistics of the Centers for Disease Control, is a household‐based, yearly survey evaluating and quantifying the self‐reported health status of United States' residents . This survey has been used to determine the basic prevalence of many health conditions on a national basis, including several in otolaryngology, such as sinusitis and balance disorders . In the 2012 cycle of the NHIS, a supplement was contained within the survey specifically pertaining to adult voice, speech, and language disorders, with targeted, specific questions related to respondents' voice problems.…”
Section: Introductionmentioning
confidence: 99%